Foreign Affiliates and Technology Spillovers in the French Manufacturing Sector: An Analysis using Panel Data - Lafi, Mosbah (International Journal of Economics and Financial Issues, 2018)
The question of whether foreign direct investment (FDI) contributes to the enhancement of technological capacities of foreign firms operating in host countries has long captured the attention of economists and politicians. Still more intriguing is the question of determining what are the most effective methods of technology transfer. In that light, the econometric study presented here has drawn on a panel database of French firms covering the period from 2008 to 2010. Horizontal and vertical FDI spillovers are examined in upstream markets while considering their impact on the productivity of local firms. Our results show that vertical technological spillovers occur across all industry sectors whereas evidence of horizontal spillovers is revealed solely in medium- and high-tech industries. Hence, it can be said that these spillovers are inversely proportional to the technological effort exerted by domestic firms in terms of R&D expenditures. Similarly, domestic firms with an international outlook seem to have a greater capacity to absorb foreign technology. Keywords: Foreign direct investment, technology spillovers, vertical linkages, horizontal linkages, French manufacturing sector, panel data. JEL Classifications: F23. L00. O33.